Trastorno por deficit de atención e hiperactividad y su influencia en el comportamiento de un niño de 9 años de edad de la ciudad de Babahoyo - Montenegro Burbano, Geraldine Yuliethe (2021)
Attention deficit hyperactivity disorder is a pathology currently widely found in the neurological development of children and adolescents, which has very important behavioral, academic, psychological and social repercussions, which is greatly appreciated by both the sufferer and of his family. This disorder is characterized by significantly affecting the areas of development of the child or adolescent, such as the cognitive area, compromising difficulties in concentration, and memory; the affective area where the child experiences irritability, impulsivity, demotivation, high and variable mood; the social and school area presenting difficulty in performing tasks, abiding by rules and hyperactivity and the somatic area where the child presents physical diseases such as headaches when experiencing such significant symptoms of ADHD. The present case study aims to document the therapeutic process carried out in a minor diagnosed with ADHD with combined presentation, for this purpose data regarding the evaluation are provided, through the use of a psychometric battery administered to the child in addition to the use of one of the most effective therapies to carry out the treatment of this disorder, cognitive / behavioral therapy, which was implemented during the intervention process, in order to reduce the behavior and attention problems that are difficult for the patient at the time to learn and abide by rules within the home.